PERBANDINGAN TEKANAN DARAH SISTOLIK DAN DIASTOLIK PADA KEJADIAN STROKE - Nurdjaman Nurimaba (Neurona Majalah Kedokteran Neuro Sains, 2009)
INTRODUCTION HYPERTENSION IS A STRONG PREDICTOR FOR STROKE INTRACEREBRAL HEMORRHAGE OR INFARCTION PREVIOUSLY DIASTOLIC HYPERTENSION ONLY BECOME STRONG PREDICTOR IN STROKE PATIENT BUT IN THE DATA OF ISOLATED SYSTOLIC HYPERTENSION DIASTOLIC TENSION LESS THAN 90MMHG INTRACEREBRAL HEMORRHAGE MOSTLY OCCURRED THE PURPOSE OF THIS INVESTIGATION TO KNOW LIMITATION OF SYSTOLIC AND DIASTOLIC HYPERTENSION CORRELATION WITH INTRACEREBRAL AND ATHEROTROMBOTIC STROKE